New records of oribatid mites from Mexico with description of a new species - Revelo-Tobar, Harol; Estrada-Venegas, Edith G.; Martinez, Armando Equihua (Zootaxa, 2022)
The present taxonomic study was carried out with material collected in the Michoacán state, Mexico, during one year of sampling. Ten new records of oribatid mites are reported for Mexico. Also, a new species, Gustavia mexicana sp. nov., is described, which differs from Gustavia fusifer (Koch, 1841), G. transylvanica Mahunka, 2006, G. latolamellata Hammer, 1977 and G. magnifica Golosova et Karppinen, 1984 by the absence of setal alveolus c, shape of sensillum, size and shape of rostrum, shape of lamella and presence of sejugal suture, respectively. A detailed description, schemes and photographs of the new species and an identification key for the species of the genus are provided.